Fingerprint kernels for protein structure comparison - Fober, T.; Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (Molecular Informatics)

Comparing fuzzy partitions: A generalization of the Rand index and related measures - Hüllermeier, Eyke; Rifqi, M.; Henzgen, Sascha; Senge, Robin (IEEE Transactions on Fuzzy Systems)

Fuzzy Pattern Trees: Ein alternativer Ansatz zur Fuzzy-Modellierung - Senge, Robin; Fober, T.; Nasiri, N.; Hüllermeier, Eyke (At-Atomatisierungstechnik)

Multiphoton state engineering by heralded interference between single photons and coherent states - Bartley, Tim; Donati, Gaia; Spring, Justin B.; Jin, Xian-Min; Barbieri, Marco; Datta, Animesh; Smith, Brian J.; Walmsley, Ian A. (Physical Review A)

Carbon Fibre Prepregs: Simulation of a Thermo-Mechanical-Chemical Coupled Problem - Hankeln, Frederik; Mahnken, Rolf (PAMM)

Theoretical investigation of the enzymatic phosphoryl transfer of β-phosphoglucomutase: revisiting both steps of the catalytic cycle - Elsässer, Brigitta; Dohmeier-Fischer, Silvia; Fels, Gregor (Journal of Molecular Modeling)

Logik - Einführung in das Denken - Krimphove, Dieter

Asynchronous Occlusion Culling on Heterogeneous PC Clusters for Distributed 3D Scenes - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
We present a parallel rendering system for heterogeneous PC clusters to visualize massive models. One single, powerful visualization node is supported by a group of backend nodes with weak graphics performance. While the visualization node renders the visible objects, the backend nodes asynchronously perform visibility tests and supply the front end with visible scene objects. The visualization node stores only currently visible objects in its memory, while the scene is distributed among the backend nodes’ memory without redundancy. To efficiently compute the occlusion tests in spite of that each backend node stores only a fraction of the original geometry, we complete the scene by adding highly simplified versions of the objects stored on other nodes. We test our system with 15 backend nodes. It is able to render a ≈ 350,M polygons (≈ 8.5,GiB) large aircraft model with 20, to 30,fps and thus allows a walk-through in real-time.

Geführte akustische Wellen zur Flüssigkeitscharakterisierung - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Numerische Nullstellensuche in Determinantenfunktionen mittels Intervallarithmetik und algorithmischem Differenzieren - Bause, Fabian; Walther, Andrea; Henning, Bernd